Modification of poly(methyl vinyl ether - alt - maleic anhydride) with pregabalin drug active substance via ring opening polymerization of anhydride ring in/noncatalyst media - Cakiral, Kadir; Sakar, Dolunay (SPRINGER, 2023)
Pregabalin is widely used in neurologic diseases such as epilepsy treatments and has a low half - life in the body when taken in tablet form by mixing physically with some matrix. In order to prolong therapeutic effect of pregabalin in system by means of protecting the stability and activity of pregabalin, poly(methyl vinyl ether - alt - maleic anhydride) copolymer is functionalized with pregabalin. For this purpose, it is synthesized 6 copolymer - drug delivery systems which pregabalin drug active material bonded to poly(methyl vinyl ether - alt - maleic anhydride) copolymer in 3 different ratios in uncatalyzed media and in triethylamine catalyst media. The approximate molecular weight of copolymer-drug delivery systems and percent drug binding to copolymer are calculated together with the structural characterization of the synthesized copolymer-drug delivery systems by FT-IR/ATR and (1) H NMR spectroscopy and morphological characterization via SEM, XRD and BET analysis. To determine the optimum conditions in which these copolymer-drug delivery systems are stable, zetasizer measurements such as particle size and zeta potential are made in different pH and artificial body fluids as a function of time at 37 celcius. The optimum conditions at which these copolymer-drug delivery systems maintain their activity are determined by UV-VIS spectrum measurements in different pH and artificial body fluid environments depending on time.
Keywords: Poly(methyl vinyl ether-alt-maleic anhydride) copolymer; Pregabalin; Copolymer-drug delivery conjugated system; Stability and activity; MALEIC-ANHYDRIDE; DELIVERY SYSTEMS; POLY(ANHYDRIDE) NANOPARTICLES; COPOLYMERS; ACID; Polymer Science